The South African Adventure Tourism Economy: An urban phenomenon - McKay, Tracey McKay (Bulletin of Geography. Socio-economic Series, 2017)
The international adventure tourism literature is remarkably silent on the geographical nature of the industry. This study seeks to provide a geographical analysis of the sector within the context of South Africa. The spatial analysis was undertaken by metropolitan area, secondary towns and small towns, using a dataset of adventure tourism enterprises. It was found that the sector is spatially concentrated and highly urbanised, despite the perception that adventure tourism requires wild and outdoor spaces. With many adventure tourism enterprises located in South Africas metropolitan areas, it is a hither too unknown sub-sector of the South African urban tourism market. Urban settlements with large populations and a strong general tourism sector form a significant support base for adventure tourism operators. Cape Town is the dominant adventure tourism destination, making it the adventure capital of South Africa. A few small settlements were found to be highly dependent upon the sector for survival.